Processes of State, Class and Ethno-Racial Formation in Urban Malaysia: Geo-Spatial Transformations and Regime Shifts 1970-2000 - Nonini, Donald M. (Anthropologica, 2022)
This article is a historico-ethnographic reconstruction of the simultaneously interconnected processes of postcolonial state, class and ethno-racial formation in Malaysia, as these were refracted in the daily lives of ethnic Chinese in one Malaysian city over a 30-year period (1970-2000). The projects of the dominant Malay ethno-racial fraction of the ruling elite to deflect class struggles, protect capital and consolidate its class interests through state expansion have become visible as aspects of space (Lebfebvre 1974) in the built environment of the city, as have the dialectical responses of resistance and emigration by the city's Chinese residents to these projects.